Detection and cognitive-behavioral therapy in young adults with generalized social phobia - Macià Antón, Diego; Olivares Olivares, Pablo J.; Amorós Boix, Maravillas (Anales de Psicología / Annals of Psychology, 2012)
The objective of this experimental study is to adapt and validate for implementation in the adult Spanish population (young adults) the multicomponent treatment Cognitive-Behavioral Group Therapy (CBGT; Heimberg, 1991) that has been proved to be effective in the treatment of social phobia in adults in other countries. We present the results obtained with an experimental treatment group composed of 17 participants (aver- age age: 19.06 years, DT: 0.89935) that were compared with a wait list con- trol group (n= 16) (average age: 19.63 years, DT: 0.6914) all university students with generalized social phobia (APA, 2002). The assessment was carried out before and after treatment as well as in two follow-ups carried out six and twelve months later. The results show both the short-and long-term effectiveness of the program in all the measures to evaluate anxiety and social avoidance. However, the participants of the control group did not reach statistically significant improvements for any of the variables measured.